MANAJEMEN STRATEGI DALAM MENINGKATKAN MUTU PELAYANAN KEPEGAWAIAN - Hefniy, Hefniy; Fairus, Refi Najma (JURNAL AL-TANZIM, 2019)
Strategy Management in improving the quality of staffing services in the Probolinggo District Education Office. The purpose of this article was to study the management of strategies carried out by the Education Office of Probolinggo District specifically service personnel and the quality of staffing services from the implementation of the management strategies in the Probolinggo District Education Office. This study uses qualitative methods with a type of case study research. The data analysis used is the Interactive analysis model of Miles and Huberman. The results is showed that the management strategy carried out by the Probolinggo District Education Office was also applied to staffing services guided by the Provincial RPJP and Probolinggo District RPJMD using a strategic planning process, implementing strategies and evaluation strategies. And the quality of the Probolinggo District Education Office staffing services after the strategy management has been fairly good with reference to the fulfillment of five service standards.